Carbon, Nitrogen, and Noble Gas Isotopes Reveal Deep Volatile Signatures in Thermal Springs in the Central Volcanic Zone (Cvz) of the Andes - Blamey-Alegria, J (Elsevier B.V., 2025)
In subduction zones, thermal springs release deeply-sourced volatiles from Earth s mantle, crust, and/or subducted slab-derived material. The origin and apparent ages of these volatiles are important for understanding the deep volatile cycle, which in turn affects the distribution of microbial life in the subsurface. Here, we report carbon (13C, 14C), noble gas (He, Ne, Ar, Kr and Xe), and clumped nitrogen isotope data in gas and water samples from thermal springs within the Central Volcanic Zone (CVZ) of the Andean Convergent Margin (ACM). He isotopes show that CVZ gases are predominantly sourced from the crust (∼77 %), with smaller mantle contributions (∼23 %), consistent with previous studies from the CVZ. Thermal spring samples with non-atmospheric He-Ne characteristics have low 14C activities, and are deeply derived (i.e., from the mantle and crust) and old (>22,000 years). To gain additional constraints on volatile sources, a gas sample from Pirquitas Argentina was analyzed using a new high-precision technique to reveal significant geogenic anomalies in argon (40Ar/36Ar = 492), fissiogenic xenon (88 % crustal), and helium (84 % crustal) isotopes. Clumped N2 isotopologue results also indicate that the N2-rich Pirquitas sample is dominated by crustal and magmatic N2, which was unambiguously released at high temperatures (indicated by Δ30 of ∼0‰). When taken together, all carbon, noble gas and clumped N2 isotope data from CVZ thermal springs point toward a predominantly crustal source of volatile elements, which is consistent with the thick crust beneath the arc. We conclude that thermal springs with noble gas isotopic evidence for minimal air contributions are old, suggesting that any microbial communities entrained in them are also supported by deeply-derived and old organic carbon. © 2024